Penerapan SAK EMKM dalam Penyusunan Laporan Keuangan Usaha Katering: Studi Kasus - Emilia, Lea; Salman, Putriana; Renny Aprilia (Indonesian Journal of Applied Accounting and Finance, 2025)
MSMEs play a very important role as the backbone of the Indonesian economy, driving and increasing national economic growth sustainably. CV Maha Rasa has been enageged in the catering sector since 2009 in Banjarmasin. Its financial transactions include : (1) credit sales, (2) cash and credit purchases of raw materials, (3) cash purchases of spices, packaging, and gas, (4) payment of employee salaries, and (5) payment of electricity, water, and internet. CV Maha Rasa has not prepared financial report. Financial records are ini the form of Cash Books, Account Receivable Subsidiary Books, Account Receivable Reports, Accounts Payable Subsidiary Books, and Accounts Payable Report. This study aims to prepare catering financial reports based on “SAK Indonesia Untuk EMKM” at CV Maha Rasa. This study uses a qualitative research type with a case study approach and uses data collection methods, namely interviews, observations, and documentation. The results of the study were ini the form of preparation of financial statements in accordance with “SAK Indonesia Untuk EMKM”, consisting of Income Statements, Financial Position Report, and Notes to Financial Statements, with monthly periods (as of January 31, 2025; as of February 28,2025; and as of March 31, 2025) and the first quarter as of March 31, 2025, which went through all accounting cycles sequentially. the result of this study can be used by CV Maha Rasa in evaluasting its financial performance. This study shows the preparation of comprehensive financial statements combined with cost accounting for two departemens. Kata Kunci: Financial Report; Manufacturing Company; SAK Indonesia Untuk EMKM. @IJAAF 2023